2020
DOI: 10.1039/d0cp04076b
|View full text |Cite
|
Sign up to set email alerts
|

Transport phenomena of Cu–S–Te chalcogenide nanocomposites: frequency response and AC conductivity

Abstract: In this communication, development and electrical characterization of some chalcogenide nanocomposites have been reported. X-ray diffraction (XRD) has been studied to reveal microstructure of them. Mott’s variation range hopping model...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…Some focus on the intrinsic properties of the materials, while others highlight applications such as photovoltaic cells, light-emitting diodes, and transparent transistors. Compared to these large families of materials, chalcogen-based wide-band-gap semiconductors (Ch = S, Se, Te) ( E g > 2 eV) are characterized by their propensity for p-type doping, high mobility, high valence-band positions, and lower ionization energies. However, compared to M–O bonds, the weaker M–Ch (with Ch = S, Se, Te) bonds in these materials may lead to increased degradation and stability concerns in chalcogenides …”
Section: Introductionmentioning
confidence: 99%
“…Some focus on the intrinsic properties of the materials, while others highlight applications such as photovoltaic cells, light-emitting diodes, and transparent transistors. Compared to these large families of materials, chalcogen-based wide-band-gap semiconductors (Ch = S, Se, Te) ( E g > 2 eV) are characterized by their propensity for p-type doping, high mobility, high valence-band positions, and lower ionization energies. However, compared to M–O bonds, the weaker M–Ch (with Ch = S, Se, Te) bonds in these materials may lead to increased degradation and stability concerns in chalcogenides …”
Section: Introductionmentioning
confidence: 99%
“…This experiment demonstrates that the hopping process is the only factor that affects conductivity [60] . Higher values of n would suggest the motion of a small polaron in the current nano glassy system is percolation type [60–62,23–24,37] …”
Section: Resultsmentioning
confidence: 69%
“…[60] Higher values of n would suggest the motion of a small polaron in the current nano glassy system is percolation type. [60][61][62][23][24]37] We have observed that DC activation energy (E σ ), and activation energy (E H ) for hopping frequency (ω H ) increases with increasing Fe content in glass system based on xFe ⋅ (1-x) (0.3 V 2 O 5 ⋅ 0.2MoO 3 ⋅ 0.4CdO ⋅ 0.1ZnO) [x = 0.0, 0.05, 0.10] compare with other glassy systems [12,[23][24][53][54]56] (Table 1).…”
Section: Ac Conductivitymentioning
confidence: 99%
“…The dielectric properties can be analyzed via complex electric modulus formalism M* (ω) which permits to study charge transport processes. [37,38] It is defined as the inverse of complex permittivity process ε Ã ðωÞ admitted as [39,40]…”
Section: The Electrical Modulus Formalismmentioning
confidence: 99%